2023
DOI: 10.1186/s42826-022-00152-1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the intestinal epithelial barrier during laxative effects of phlorotannin in loperamide-induced constipation of SD rats

Abstract: Background Disruptions of the intestinal epithelial barrier (IEB) are frequently observed in various digestive diseases, including irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD). This study assessed the improvement in the IEB during the laxative activity of phlorotannin (Pt) harvested from Ecklonia cava in constipation by examining the changes in the expression of the regulatory proteins for the tight junction (TJ) and adherens junction (AJ), and inflammatory cytokines in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The proper functioning of the intestines is closely linked to the maintenance of the intestinal epithelial barrier. This barrier can become compromised in chronic constipation [ 34 ]. AS-IV has been shown to improve the dysfunction of the intestinal barrier in different types of diseases [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proper functioning of the intestines is closely linked to the maintenance of the intestinal epithelial barrier. This barrier can become compromised in chronic constipation [ 34 ]. AS-IV has been shown to improve the dysfunction of the intestinal barrier in different types of diseases [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many other reported wide-ranging health benefits for E. cava extracts or fractions. For example, a review by Kim et al (2023) states that the Korean Ministry of Food and Drug Safety approved the use of an E. cava supplement containing phlorotannin as a health-functional product that helps improve sleep quality. The paper covers the sedative-hypnotic mechanisms in animal models as well as human clinical trials.…”
Section: Colored Corn Floursmentioning
confidence: 99%
“…Li et al [39] found that administering the E. cava component dieckol to the inner ear of rats prevented ototoxic hearing loss, suggesting that the procedure may be a safe and effective method to prevent drug-induced hearing loss. Park et al [40] reported that a water extract of E. cava acts as a potential therapeutic agent against fine dust induced health damage in mice by regulating gut function of the microbiota and Kim et al [41] provides evidence for the use of phlorotannin against constipation in rats.…”
Section: Colored Corn Floursmentioning
confidence: 99%
“…2023, 24, 15757 2 of 24 chemicals and diet, were widely applied to produce animal models with constipation phenotypes. In most cases, the human-like constipation was successfully induced by the oral administration or subcutaneous injection of loperamide (Lop) hydrochloride as well as by the feeding of a low-fiber diet containing 41.5% cornstarch, 24.5% milk casein, 10.0% sucrose, 10.0% dextrin, 7.0% mineral mixture, 6.0% corn oil, and 1.0% vitamin mixture for 5 weeks [8][9][10][11]. Also, the phenotypes for constipation could be induced by treatment with opioids and carbon, although these methods are rarely used [12,13].…”
Section: Introductionmentioning
confidence: 99%